Femoral bowing deformity: possible aetiologies in a 14th-19th century skeleton from Constância (Portugal) - Assis, Sandra (2016)
In the years of 2002 and 2003, 151 skeletons (106 adults and 45 non adults) were unearthed from the ancient necropolis of São Julião Church (Constância, Portugal) dated from the 14th-19th centuries. Of the individuals analysed, one in particular, an adult female (Sk. 31) exhibited an abnormal femur morphology. Macroscopically the bone lesions were characterized by a bilateral antero-posterior thinning of the shaft and an antero-lateral bending of the proximal third of the femur diaphysis. An increased cortical thickness in the concave side of the femur shaft was revealed through conventional X-ray analysis. In addition with the described bone changes, the individual also showed small bone nodes on the inner surface of the frontal bone and an undisplaced calcaneocuboid fracture on the left calcaneus. Although femoral bowing deformity is a common manifestation in many vitamin D deficiencies (i.e. residual rickets or osteomalacia), other conditions, such as physiological bowing deformities or coxa vara, may also produce similar long bones features. The aims of the present case-study are to present the main possible etiologies for the skeletal changes observed, as well as to discuss the impact of postmortem damage in the differential diagnosis.